2014
DOI: 10.1111/tan.12449
|View full text |Cite
|
Sign up to set email alerts
|

MIC gene polymorphism and haplotype diversity in Li nationality of Southern China

Abstract: Here, we report for the first time the polymorphisms of MICA and MICB in a healthy Li population of 344 unrelated individuals. By using polymerase chain reaction-sequence specific priming (PCR-SSP) and sequence-based typing (PCR-SBT), 17 MICA-sequence alleles and 5 MICA-STR (short tandem repeats, STR) alleles, as well as 17 MICB alleles were detected, among which MICA*010, MICA*A4 and MICB*005:02 were the most frequent alleles. In addition, linkage disequilibrium was investigated and the most common two-locus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
(54 reference statements)
1
4
0
1
Order By: Relevance
“…Regarding the allele frequency, MICA*A5 was the most common MICA‐STRs followed by MICA*A5.1, which was in line with the observations in other Han Chinese populations 26,32,33 . The data of Hainan Li population were similar to Lin et al reported before 34 …”
Section: Discussionsupporting
confidence: 90%
“…Regarding the allele frequency, MICA*A5 was the most common MICA‐STRs followed by MICA*A5.1, which was in line with the observations in other Han Chinese populations 26,32,33 . The data of Hainan Li population were similar to Lin et al reported before 34 …”
Section: Discussionsupporting
confidence: 90%
“…Similar to what has been hypothesized for HLA genes , this restricted polymorphism may be due to a genetic bottleneck created by disease outbreak and/or population settlement/migration. MICA*001 , MICA*020 , MICA*045 , and MICA*052 are specific to Europeans , South American Indians , Chinese , and Thais , respectively. The fact that these alleles are abundant just in a specific region of the planet indicates that certain alleles may give rise to more specialized proteins in a given localized microbial environment (although migratory influences could also play a role).…”
Section: Polymorphism Of Mica and Micbmentioning
confidence: 99%
“…The following populations were included for frequency calculations. MICA : Thailand: Northeastern Thais ; Japan ; China: Li nationality of Southern China , Zhuang nationality of Southern China , Southern Han population , Han population , Northern Han population ; Africa: North Morocco ; Nigerian ; Europe: Southeastern Spain , France , Slovakia , Austria ; South America: Southwest Brazil Amerindians , European Brazilians, Euro‐Brazilian from Parana State, Southeast of Brazil , Sao Paolo , South American Indians ; North America: North American Caucasians , African Americans . MICB : China: Southern Chinese Han , Northern Chinese Han , Zhejiang Han ; Europe: Spain and Wales ; Korea .…”
Section: Polymorphism Of Mica and Micbmentioning
confidence: 99%
“…A dendrogram based on the Nei's standard genetic distances between the 12 populations, which were calculated using MICB gene coding region frequencies, was constructed by the neighbor‐joining (NJ) method using the Mega 7.0 . Frequency data for other populations, Hunan Han, Inner Mongolia Han, Zhejiang Han, Zhuang, Li, Tujia, Mongolian, Yao, Korean, Spanish, and Welsh, were obtained from previous studies. Comparison of frequencies at MICB loci between the Jing and other populations was performed by contingency test using GraphPad Prism (http://www.graphpad.com/quickcalcs/contingency1).…”
Section: Frequency Distribution Of Micb Polymorphisms In 150 Jing Submentioning
confidence: 99%